2023
DOI: 10.1002/mnfr.202200623
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Wild Olive (Acebuche) Oil as a Pharm‐Food to Prevent Ocular Hypertension and Fibrotic Events in the Retina of Hypertensive Mice

Álvaro Santana‐Garrido,
Claudia Reyes‐Goya,
Helder André
et al.

Abstract: ScopeOur laboratory has previously described the antioxidant and anti‐inflammatory potential of a wild olive (acebuche, ACE) oil against hypertension‐associated vascular retinopathies. The current study aims to analyze the antifibrotic effect of ACE oil on the retina of hypertensive mice.Methods and resultsMice are rendered hypertensive by administration of NG‐nitro‐L‐arginine‐methyl‐ester (L‐NAME) and simultaneously subjected to dietary supplementation with ACE oil or a reference extra virgin olive oil (EVOO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 64 publications
(82 reference statements)
1
4
0
Order By: Relevance
“…The ameliorative effects exerted on the glaucomatous retina by an ACE oil-enriched diet do not appear to rely on IOP reduction in the MCE model; similar results were previously obtained in rodent glaucoma models treated with other nutraceutical compounds [32,46,53,95]. Nevertheless, Santana-Garrido et al recently described the ability of ACE oil-enriched diet to restore IOP levels in Nω-nitro-L-arginine methyl ester (L-NAME)-treated hypertensive mice [28]. L-NAME is able to inhibit nitric oxide synthases, particularly reducing endothelial nitric oxide production and thus inducing systemic vasoconstriction [96].…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…The ameliorative effects exerted on the glaucomatous retina by an ACE oil-enriched diet do not appear to rely on IOP reduction in the MCE model; similar results were previously obtained in rodent glaucoma models treated with other nutraceutical compounds [32,46,53,95]. Nevertheless, Santana-Garrido et al recently described the ability of ACE oil-enriched diet to restore IOP levels in Nω-nitro-L-arginine methyl ester (L-NAME)-treated hypertensive mice [28]. L-NAME is able to inhibit nitric oxide synthases, particularly reducing endothelial nitric oxide production and thus inducing systemic vasoconstriction [96].…”
Section: Discussionsupporting
confidence: 61%
“…Indeed, ACE oil shows a higher quantity of sterols, tocopherols (e.g., vitamin E) and triterpene acids compared to the classic extra-virgin olive oil [26,89]. In this respect, a recently published work showed that in a mouse model of glaucoma ACE oil have better retinoprotective activity than a reference extra-virgin olive oil in terms of antioxidant, anti-inflammatory and antifibrotic effects, suggesting that the peculiar composition of ACE oil may be responsible for its improved features [28]. Among these components, vitamin E is a powerful fat-soluble antioxidant that is able to prevent the oxidation of polyunsaturated fatty acids in cell membranes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations